A construção de um sistema de espaços livres para Colatina-ES - Simões, Renata Mattos (2016)
The dissertation proposes a descriptive and analytical research of the open spaces system in the city of Colatina-ES, focusing on the relationship between the distribution, type and amount of open space in the territory, territorial planning and ecologica